Inhibition of NLRP3 Inflammasome: A Prospective Target for the Treatment of Ischemic Stroke - Feng, Ya-Shuo; Tan, Zi-Xuan; Wang, Man-Man; Xing, Ying; Dong, Fang; Zhang, Feng (Frontiers in Cellular Neuroscience, 2020)
Stroke is one of the major devastating diseases with no effective medical therapeutics. Because of the high rate of disability and mortality among stroke patients, new treatments are urgently required to decrease the brain damage following stroke. In recent years, the inflammasome is a novel breakthrough point that play an important role in the stroke, and the inhibition of inflammasome may be an effective method for stroke treatment. Briefly, inflammasome is a multi-protein complex that causes activation of caspase-1 and subsequent production of pro-inflammatory factors including interleukin (IL)-18 and IL-1β. Among them, the NLRP3 inflammasome is the most typical inflammasome, which can detect cell damage and mediate inflammatory response to tissue damage in ischemic stroke. The NLRP3 inflammasome has become a key mediator of post-ischemic inflammation, leading to a cascade of inflammatory reactions and cell death eventually. Thus, NLRP3 inflammasome is an ideal therapeutic target due to its important role in the inflammatory response after ischemic stroke. In this review, we will summarize the structure, assembly and regulation of NLRP3 inflammasome, the role of NLRP3 inflammasome in ischemic stroke, and several treatments targeting NLRP3 inflammasome in ischemic stroke. The further understanding of the mechanism of NLRP3 inflammasome in patients with ischemic stroke will provide novel targets for the treatment of cerebral ischemic stroke patients.